The Effect of Immune Cell Abnormalities in the Pathogenesis of Chronic Prostatitis / Chronic Pelvic Pain Syndrome - Xuan, Yang; Duan, Yue (Journal of Liaquat University of Medical & Health Sciences, 2025)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a prevalent urological condition with high incidence, complicated etiology, and unsatisfactory treatment. It seriously affects the quality of life of patients, and the pathogenesis of the disease is still not clear. This paper reviews the recent progress of research on the effect of immune cell abnormalities in CP/CPPS.